Pengaruh Service Quality dan Customer Perceived Value terhadap Customer Satisfaction Dimediasi oleh Trust - Miftahul Jannah Al Kutubi; Ritta Setiyati (JURNAL RISET MANAJEMEN (JURMA), 2025)
Customer satisfaction plays an important role in marketing strategies that can be implemented by the banking industry by providing the best facilities for its customers to be able to provide value and experience of the services provided so that trust increases. The aim of this research was to measure more specifically service quality and customer perceived value towards trust in customers using the Livin Mandiri application. This type of research is quantitative with a purposive sampling technique distributed through questionnaires to 100 male and female Livin Mandiri mobile banking user respondents aged 20 - 55 years and domiciled in West Jakarta. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this research show that the variables Service Quality, Customer Perception Value, Customer Satisfaction and Trust are proven to have a positive effect and the service quality variable has the greatest influence on trust. Then the biggest indirect influence is trust with service quality and customer satisfaction. This research contributes to the banking industry in maintaining and increasing customer satisfaction by looking at several factors in consumer complaints in an optimal and measurable manner. For further research, researchers suggest expanding the research area and looking for objects in other fields.